Effect of Printing Speed on the Properties of 3D Printed Products Using Recycled PET Filament - Deni Fajar Fitriyana; Agung Efriyo Hadi; Nugroho Suhodo; Aldias Bahatmaka; Januar Parlaungan Siregar; Tezara Cionita; Zuhriyan Ash Shiddieqy Bahlawan; Achmad Yanuar Maulana (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Recycled PET has been widely studied for its potential use in 3D printing applications. However, few research has examined how printing speed affects recycled PET filament products' mechanical and physical qualities. This research examines how printing speed influences the physical and mechanical qualities of 3D-printed PET filament goods created from mineral water bottle trash. In this study, filament fabrication is carried out using the homemade pultrusion machine, then the filament is used for 3D printing with variations in printing speed (30, 45, and 60 mm/s). The conducted tests comprise density, tensile, hardness, and compressive testing to examine their physical and mechanical properties. This research found that 45 mm/s printing produced specimens with the maximum density, tensile strength, and hardness. The material reached a density of 0.968 g/cm³, tensile strength of 15.752 N/mm², and hardness of 43.50 Shore D under these circumstances. In contrast, specimens printed at 30 mm/s and 45 mm/s showed the greatest (10.841 N/mm²) and lowest (6.510 N/mm²) compressive strengths. The density, hardness, and tensile strength of 3D-printed specimens improved as the printing speed increased from 30 to 45 mm/s. Printing rates above 45 mm/s reduced specimen density, hardness, and tensile strength. This work promotes sustainable manufacturing by showing that recycled PET filament may be used for 3D printing and how printing speed affects material qualities, thereby promoting sustainable production practices and reduce dependence on virgin materials.